SMOKING BAN SURVEY AMERICAN ASSOCIATION OF RESPIRATORY CARE 890620 210 CHOB (Tufts Archival Research Center, 2007)
Agenda for meeting of the American Association of Respiratory Care concerning a survey on a smoking ban aboard aircraft.